(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Rules of Engagement (ROEs) are orders released to military units which define the circumstances, conditions, degree and manner in which a combatant is allowed to use force. ROEs create the “space of conflict and battle” also known as “Agramante´s Camp”, which is operational, physical, mental, legal and ethical in nature. We have focused on an analysis of some of these aspects in order to better comprehend their nature, thus developing a political science research in several areas. Firstly, we have looked into their formal structure, presenting an approach to their cybernetic and algorithmic feature, as well as how they function as a language. We conceive see them as “political machines”, a specific postmodern concept, in line with the famous dictum “the map is not the territory”. ROEs have not been accepted without opposition, a phenomenon we have dubbed the “Z effect”. The article concludes with an overview of the relationship between ROEs and collateral damage and the construction of reality through discourse